Coesão discursiva nos Estudos de execução transcendental de Liszt: as últimas sete peças - Bento, Daniel (Escola de Música da UFMG, 2010)
It seems to be urgent the investigation upon the cohesive processes in the Transcendental studies by Franz Liszt: the emergence of a unified whole is already suggested in the tonal plan that coordinates them. The examination of other aspects that could guarantee unity - related to specific materials of the compositions - is this text's main concern. Its focus is the subset formed by the last seven pieces of the group, and that is justified by the fact that they show a particular affiliation, the ascending leap of sixth preceded by different forms of emphasis. The theoretical basis adopted is an adaptation of Dahlhaus' concept of subthematicism, which supports the methodological procedure: the analytical approach. The results show connections based not only on harmonic phenomena, but also on the recurrence of flexible materials that are object of transformations. Hence, it is possible to substantiate the cohesion of the selected pieces and the relevance of the integration processes in Liszt's volume.

Parece urgente a investigação dos processos de coesão nos Estudos de execução transcendental de Franz Liszt: a emergência de um todo unificado é sugerida já no plano tonal que os coordena. O exame de outros aspectos que pudessem garantir unidade - vinculados aos materiais específicos das composições - constitui o foco do presente trabalho. Seu recorte é o subconjunto formado pelas últimas sete peças do grupo, justificado pelo fato de elas demonstrarem uma afinidade particular, o salto de sexta ascendente antecedido por diferentes formas de ênfase. O fundamento teórico adotado é uma adaptação do conceito de subtematismo de Dahlhaus, que nutre o procedimento metodológico: a abordagem analítica. Os resultados mostram conexões baseadas não apenas em fenômenos harmônicos, mas também na recorrência de materiais flexíveis que sofrem transformações. Com isso, confirma-se a coesão dos recortes e a pertinência dos processos de integração no volume de Liszt.
Discourse cohesion in Liszt's Transcendental studies: the last seven pieces
Keywords: musical analysis; musical cohesion; subthematicism; Franz Liszt; análise musical; coesão musical; subtematismo; Franz Liszt